2022
DOI: 10.3389/fimmu.2022.974087
|View full text |Cite
|
Sign up to set email alerts
|

The role of immune profile in predicting outcomes in cancer patients treated with immunotherapy

Abstract: BackgroundDespite the efficacy of immunotherapy, only a small percentage of patients achieves a long-term benefit in terms of overall survival. The aim of this study was to define an immune profile predicting the response to immune checkpoint inhibitors (ICIs).MethodsPatients with advanced solid tumors, who underwent ICI treatment were enrolled in this prospective study. Blood samples were collected at the baseline. Thirteen soluble immune checkpoints, 3 soluble adhesion molecules, 5 chemokines and 11 cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Furthermore, each individual molecule could present several dynamic positive or negative interactions in a network immunological context. Each individual molecule has multiple molecules with which it can interact, a bidirectional signaling is possible and, depending on the context, a single molecule could be pro-inflammatory or anti-inflammatory [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, each individual molecule could present several dynamic positive or negative interactions in a network immunological context. Each individual molecule has multiple molecules with which it can interact, a bidirectional signaling is possible and, depending on the context, a single molecule could be pro-inflammatory or anti-inflammatory [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IL-1β induced sPD-L1 release [ 86 ]. Elevated IL-1β and sPDL-1 levels showed a significantly shorter progression-free survival in BC patients [ 89 ], highlighting the beneficial impacts of targeting IL-1β in both HR+ and TNBC patients. It has been shown that BC is a systemic inflammatory disease [ 3 , 4 , 5 ], where peripheral blood represents reservoirs and activation sites of immune cells during BC progression [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019 and 2020, FDA approved the use of atezolizumab (Tecentriq) [ 163 ] and pembrolizumab (Keytruda), a PD-1 inhibitor [ 164 ], in combination with chemotherapy in the treatment of metastatic PD-L1-positive TNBC patients [ 165 ]. Studies showed that IL-1β induced sPD-L1 release in patients with BC [ 86 ] and was correlated with significantly short progression-free survival [ 89 ]. In addition, NLRP3 contributed to immunosuppression [ 166 ] and promoted the expression of PD-L1 in various cancers including BC [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After initiation of standard cancer therapy, a panel of targetable proteins unique to a patient could constitute a framework for precision medicine. Since the type and intensity of protein-response by malignant and normal cells in the tumor microenvironment will vary among individuals, the development and inclusion of ‘therapy-induced cytokine signature’ is emerging as a new dimension of precision medicine [ 38 , 39 , 40 ].…”
Section: Cytokine Responses In Solid-tumors Therapy: An Emerging Them...mentioning
confidence: 99%